Approaches to the estimation of the level of economic security: a comparative analysis - Антонян, Олена Альбертівна; Афанасьєва, Світлана Михайлівна (Eastern-European Journal of Enterprise Technologies, 2013)
The comparative analysis of existing approaches to the estimation of the economic security level of enterprises was made. The following common approaches to the estimation were compared: indicator (threshold), resource-functional, special-purpose programme, economic and mathematical (cost), dynamic, accounting and graphical approaches, etc. Based on the analysis results, their nature, implementation stages, scientific basis, mathematical framework, positive and negative sides were determined. All this allowed to reveal that various interpretations of the basic concepts, ambiguity and diversity of principles and laws are inherent in the formation of theoretical bases of economic security. Based on various types of analysis (structural, functional, comparative, etc.), the synthesis of the obtained results, which were the basis for the concretization of establishing the criteria for the selection of indicators of the economic security level estimation such as quantification, accessibility, clarity, balance, relevance and availability of general definition, was carried out. The result of the comparison of existing approaches to the estimation of economic security of enterprises was also the definition of four groups on the estimation object: profit, threats and risks, investment, functional components.